Reverend Stephen H. Fritchman Fresno Visit - Watkins, Howard::::::::: (1978)
Channel 30 News reporter Karen Humphrey interviewing Rev. Fritchman at Unitarian Church of Fresno Used wired mic; 4144 N. Millbrook Ave., Fresno